2005
DOI: 10.1136/sti.2004.014332
|View full text |Cite
|
Sign up to set email alerts
|

The attitude of patients towards medical students in a sexual health clinic

Abstract: Objectives: To determine patient attitudes toward medical students in the sexual health clinic, and to describe factors associated with patient refusal of medical student involvement. Method: A self administered questionnaire was given to 259 consecutive patients attending the general genitourinary medicine clinic. Participants were asked to indicate their attitude to questioning and/or examination by medical students. Information was also collected on sex, age, ethnicity, and previous visits to sexual health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 5 publications
2
35
0
3
Order By: Relevance
“…Students may, understandably, feel uneasy or under-skilled in their early contacts with patients, even where patients report that they feel emotionally supported simply by the presence of medical students (Mukohara et al, 2006). Students may misjudge how sensitive patients can feel in vulnerable situations, such as a sexual health clinic, where women patients are typically less comfortable with male students, and some patients may even refuse student involvement (Ryder et al, 2005).…”
Section: Patient-centred Approaches To Medical Educationmentioning
confidence: 98%
“…Students may, understandably, feel uneasy or under-skilled in their early contacts with patients, even where patients report that they feel emotionally supported simply by the presence of medical students (Mukohara et al, 2006). Students may misjudge how sensitive patients can feel in vulnerable situations, such as a sexual health clinic, where women patients are typically less comfortable with male students, and some patients may even refuse student involvement (Ryder et al, 2005).…”
Section: Patient-centred Approaches To Medical Educationmentioning
confidence: 98%
“…Indeed, simply having exposure to medical students has been found to correlate with comfort with medical student involvement in patient care (Ryder et al, 2005). However, it is important to note that when contact with medical students is perceived as negative, this negative contact can have a lasting impact.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that past experience, especially past positive experience, increases patients' comfort with allowing students to be involved in future encounters. In fact, previous exposure to medical students was found to be correlated with comfort with medical student involvement in patient care (Ryder, Ivens, & Sabin, 2005). This comfort extends to involvement in examinations, as well as history taking and clinical interviews.…”
Section: Clinical Setting Variablesmentioning
confidence: 96%
“…A growing number of studies have reported that, generally, patients have an open and positive attitude towards medical student involvement in clinical care (Devera-sales et al 1999;Fortier et al 2006;Mavis et al 2006;Doshi et al 2006;Ryder et al 2005;Simons et al 1995;Bishop et al 1991;Ching et al 2000;O'Flynn and Rymer 2002;Shann and Wilson 2006;York et al 1995;Townsend et al 2003;Passaperuma et al 2008). In fact, among 575 patients attending community and academic-based primary care clinics, Devera-Sales et al (1999) found 90% were receptive to medical students taking part in their clinic visit.…”
Section: Introductionmentioning
confidence: 93%